Robotic Prototype and Module Specification for Increasing the Interest of Malaysian Students in STEM Education - Faridatul Ainun Zainal, Noor; Din, Rosseni; Faidzul Nasrudin, Mohammad; Abdullah, Salwani; Hadi Abd Rahman, Abdul; Norul Huda Sheikh Abdullah, Siti; Akram Zainol Ariffin, Khairul; Murnirah Jaafar, Siti; Aini Abd Majid, Nazatul (International Journal of Engineering and Technology, 2018)
The aim of this paper is to develop a robotic prototype and module specification for STEM programs through survey with STEM teachers in Malaysian schools. The target ratio for the number of students enrolling for STEM programs was not met in Malaysia for the 2015/2016 academic year. The main contributing factor is due to fear and low self-esteem although the students were qualified to pursue the STEM stream. The main objective of this paper is the development of a low-cost robotic prototype and module specification for increasing the interest of Malaysian students in STEM based on the Malaysian school curricula. To achieve this, survey forms were collected from the teachers to determine the main requirements for the modules. The main requirements identified from the survey were based on the quality of the module such as interesting, related to the Malaysian school curricula, easy to understand and implement, and low in cost. Based on these requirements, a low-cost robotic prototype and module specification were developed to promote deep learning through hands-on activities. This robotic kit has the capability to increase and sustain the interest of Malaysian students in STEM programs by providing learning-by-doing approach.Â Â